KONSEP EVALUASI PENDIDIKAN ISLAM PERSPEKTIF AL-QUR’AN BESERTA IMPLIKASINYA - Aulia Diana Devi; Seka Andrean (al-Afkar, Journal For Islamic Studies, 2021)
The Qur'an implies that the work of human evaluation is an important task in the series of educational processes carried out by educators. The focus of this research is How the basic concept of evaluation of education perspective of the Qur'an. The method used in this research with the approach of literature studies through library sources related to the concept of evaluation of education perpetif Qur'an and from various other literature sources. Then analyzed and presented the findings of the data objectively. The results showed that in this evaluation activity the system used should be based on the Quran and Sunah. Then in evaluating Islamic education requires procedures that must be used including planning, implementation, implementation monitors, data processing, reporting, and the use of evaluation results. Furthermore, in its implementation, some evaluation principles must be aimed at a good goal in a contingency, objective, thorough or comprehensive.